Reducing drudgery through operator's seat on a rotary power tiller - TIWARP, PS; NARANG, SURESH (The Indian Journal of Agricultural Sciences, 2011)
A study was undertaken during 2001-02 winter season to evaluate the field performance and quantify the reduction in drudgery owing to provision of operator's seat on power tiller for dry rotatilling. Physiological responses and psychophysical ratings were studied and data on body part discomfort were also recorded and statistically analysed. The mean values offield capacity with and without operator's seat were 0.106 and 0.115 ha/hr respectively. The corresponding fuel consumptions were 1.730 and 1.690 litre/hr. Operating cost was worked out as Rs 755 and 690/ha with and without operator's seat respectively. Mean heart rate during operation ofpower tiller with and without operator's seat were 103.2 and 129.2 beats/min respectively. The corresponding increase in heart rate over resting values were 22 and 44.5 beats/min. Statistical analysis of data indicated that increase in heart rate (HR) was significantly lower (P < 0.05) while operating power tiller with operator's seat than those without seat. Mean values of overall discomfort ratings for an operating duration of 2 hr were 5 and 6.8 with and without operator's seat respectively while corresponding body part discomfort scores were 67.3 and 99.97. There was a significant difference in overall discomfort ratings and body part discomfort scores at 5% level.